2004
DOI: 10.1136/bjsm.2003.005165
|View full text |Cite
|
Sign up to set email alerts
|

The Football Association medical research programme: an audit of injuries in academy youth football

Abstract: Objectives: To undertake a prospective epidemiological study of the injuries sustained in English youth academy football over two competitive seasons. Methods: Player injuries were annotated by medical staff at 38 English football club youth academies. A specific injury audit questionnaire was used together with a weekly return form that documented each club's current injury status. Results: A total of 3805 injuries were reported over two complete seasons (June to May) with an average injury rate of 0.40 per p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

54
393
9
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 301 publications
(471 citation statements)
references
References 19 publications
54
393
9
15
Order By: Relevance
“…Previous studies showed that young soccer players had a high risk of overuse injuries [35], an incidence of injuries increasing with age [36,37], a frequency peak of injuries at the age of 15-16 years [38], and previous injury as a high risk factor of re-injuries [39]. A study by Price et al [40] declared that greater attention should be placed to the link between musculoskeletal development and the onset of young related conditions (i.e. OsgoodSchlatter's disease), and to the increased rates of injury during preseason training and after the mid-season break.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that young soccer players had a high risk of overuse injuries [35], an incidence of injuries increasing with age [36,37], a frequency peak of injuries at the age of 15-16 years [38], and previous injury as a high risk factor of re-injuries [39]. A study by Price et al [40] declared that greater attention should be placed to the link between musculoskeletal development and the onset of young related conditions (i.e. OsgoodSchlatter's disease), and to the increased rates of injury during preseason training and after the mid-season break.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated SSC exercise performed over a prolonged period of time is likely to lead to modified musculotendon unit behaviour, altered stiffness regulation, impaired function and reduced dynamic knee stability (McLean et al 2007;Nicol et al 2006). Fatigue during soccer has been associated with increased injury risk in adult (Hawkins et al 2001) and youth football (Price et al 2004). It has been speculated that altered leg stiffness and movement control during a soccer-match contributes to the increased injury risk associated with fatigue (Cone et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Groin-related injuries tend to increase with maturation during adolescence. 10 Le Gall et al, 9 in an elite youth football academy population, documented 20.4% prevalence of osteochondral disorders affecting the pelvis in the symptomatic subjects, specifically, they reported sites of injury as: the ischium, anterior inferior iliac spine, anterior superior iliac spine, iliac crest and lesser trochanter.…”
Section: Introductionmentioning
confidence: 99%